PAYROLL SYSTEM IN SWIMMING POOL TASA USING VISUAL BASIC .NET 2003 - Parcel Natalnael Hutabarat; Rahayu Noveandini, SKom, MM (Jurnal Sistem Informasi, 2008)
With the proposed payroll system built on this design, it can replace the manual system to process payroll, and expect to be able to overcome the weaknesses that have been faced by TASA and the swimming pool is also a way to simplify payroll activities TASA which during the many weaknesses . With the system that uses computer services is expected to help TASA employee wage freeze.